2015
DOI: 10.3138/cmlr.2070.51
|View full text |Cite
|
Sign up to set email alerts
|

L1-L2 Differences in the Acquisition of Form-Meaning Pairings in a Second Language

Abstract: This paper examines the impact of L1/L2 form-meaning differences in the domain of aspect to investigate whether L2 learners are able to acquire properties of the L2 that are different from the L1. Oral data were collected from English-and German-speaking university learners of French L2 (n = 75) at two different levels of proficiency. The results show that appropriate use of aspect morphology at the advanced stages of learning is significantly influenced by differences in L1 background, with significant differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 33 publications
2
27
0
1
Order By: Relevance
“…A MAJOR FOCUS OF SECOND LANGUAGE acquisition (SLA) research to date has sought to understand the competition and relationships between a learner's different languages (Calabria et al., ). This research has repeatedly shown that the use of a single language activates a speaker's other known languages (Marian & Spivey, ; Wu & Thierry, ), that prior first language (L1) knowledge and experience can influence second language (L2) use (e.g., selective attention to linguistic cues; Ellis & Sagarra, ; MacWhinney, ), and that L1–L2 differences can influence the route and rate of L2 morphosyntactic development and processing (Avery & Marsden, 2019; Isabelli, ; McManus, , ; Murakami, ; Roberts & Liszka, ). However, despite major advances in what we know about the cognitive effects and mechanisms of learning a second language, little research has systematically examined the next step in this program: How can this understanding about the competition and relationships among a learner's different languages be used to facilitate L2 learning and teaching?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A MAJOR FOCUS OF SECOND LANGUAGE acquisition (SLA) research to date has sought to understand the competition and relationships between a learner's different languages (Calabria et al., ). This research has repeatedly shown that the use of a single language activates a speaker's other known languages (Marian & Spivey, ; Wu & Thierry, ), that prior first language (L1) knowledge and experience can influence second language (L2) use (e.g., selective attention to linguistic cues; Ellis & Sagarra, ; MacWhinney, ), and that L1–L2 differences can influence the route and rate of L2 morphosyntactic development and processing (Avery & Marsden, 2019; Isabelli, ; McManus, , ; Murakami, ; Roberts & Liszka, ). However, despite major advances in what we know about the cognitive effects and mechanisms of learning a second language, little research has systematically examined the next step in this program: How can this understanding about the competition and relationships among a learner's different languages be used to facilitate L2 learning and teaching?…”
mentioning
confidence: 99%
“…We compared three types of EI and comprehension practice designed to improve English‐speakers’ use of the Imparfait (IMP) in L2 French, a target feature well‐documented to be late‐acquired due to complex L1–L2 form–meaning mapping differences (Bartning, , ; Howard, ; Kihlstedt, ; McManus, , ): One group received EI about the L2 plus extensive comprehension practice of L2 sentences; a second group received the same L2 EI, L2 comprehension practice, plus additional comprehension practice of L1 sentences; and a third group received the same L2 EI, L2 comprehension practice, L1 comprehension practice, plus additional L1 about the EI. This design allowed us to compare (a) EI about L2 form–meaning mappings with EI about both L2 and L1 form–meaning mappings and (b) comprehension practice of L2 sentences with comprehension practice of both L2 and L1 sentences.…”
mentioning
confidence: 99%
“…Kihlstedt 2002 ;Ayoun 2004 ;McManus 2015). L'étude de l'appropriation des conjugaisons du passé s'effectue plus spécifiquement sur l'arrière-fond de deux théories qui s'opposent quant à la primauté du marquage fonctionnel par la morphologie verbale du passé : l'hypothèse aspectuelle (Aspect Hypothesis) et l'hypothèse du temps passé par défaut (Default Past Tense Hypothesis) (cf.…”
Section: Cadre Théoriqueunclassified
“…Existing evidence suggests that difficulties may arise when differences exist between the first language (L1) and second language (L2) in terms of morphosyntaxsemantics mapping (e.g., Gabriele 2009;McManus 2015). Such differences may include the manner in which meanings are marked in languages.…”
Section: Introductionmentioning
confidence: 99%
“…Such differences may include the manner in which meanings are marked in languages. For example, McManus (2015) found that German speakers learning French had some trouble with the aspectual distinctions in the target language (perfective versus habitual). The difficulty was attributed to the fact that while French marks aspect explicitly via morphemes, German marks aspect implicitly through discoursal and lexical means.…”
Section: Introductionmentioning
confidence: 99%